Moderation of Financial Constraints in Transfer Pricing Aggressiveness, Income Smoothing, and Managerial Ability to Avoid Taxation - Aristyatama, Hanung Adittya; Bandiyono, Agus (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 2 (2021), 2021)
This study examines the effect of transfer pricing aggressiveness, income smoothing, and managerial ability in tax avoidance with financial constraints as a moderating variable. The samples were manufacturing companies listed on the Indonesia Stock Exchange in 2015 to 2018. The study analyzed a form of panel data with a fixed-effect model approach. The result was transfer pricing aggressiveness and income smoothing had positives effects on tax avoidance. Managerial ability reduces tax avoidance, while financial constraints did not. Furthermore, financial constraints did not moderate the effects of transfer pricing aggressiveness on tax avoidance. Financial constraints strengthened the positive effects of income smoothing and the negative effects of managerial ability on tax avoidance. This study provides input to the tax authorities in formulating policies, as well as input for risk analysis on tax potential. Keywords: transfer pricing aggressiveness, income smoothing, managerial ability, financial constraints, tax avoidance.